8 - Research, Research Productivity and the State in South Africa* - Habib, Adam; Morrow Seán (Journal of Higher Education in Africa, 2007)
Taking the plan of action adopted at the June 2005 Department of Science and Technology conference on ‘Human Resources for Knowledge Production in South Africa’ as its starting-point, the authors of this article discuss four separate but related barriers to research productivity in South Africa: inadequate academic re- muneration and onerous working conditions; the tension that seems to have emerged between advancing equity and realising academic excellence; obstacles that under- mine institutional collaboration within the higher education and science council sectors, and the poor quality of senior managers in the knowledge system. In each case, the authors indicate the difficulties that lie in the way of reform and suggest how nevertheless the challenges can be met in contemporary South African condi- tions. They conclude that social wellbeing in general as well as the health of the research system depends on facing up to and solving these difficult and sometimes controversial issues.